Enhanced Amylase Production by Fusarium solani in Solid State Fermentation: Amylase Production by Fusarium solani - Bakri, Yasser; Jawhar, Mohammed; Eddin Arabi, Mohammed Imad (Biological Sciences - PJSIR, 2014)